Student Engagement in Small Group Discussion for English Language Learning at SMAN 1 Salimpaung - Ilahi, Puja Restu; Ratmanida, Ratmanida (Journal of English Language Teaching, 2024)
This study aims to find out the level of student engagement in small group discussions during English learning at SMAN 1 Salimpaung. The research design was conducted using descriptive research; 61 twelfth-grade students were selected using the cluster random sampling method. Questionnaires and observation checklists were used to collect data. The questionnaire consisted of 40 closed questions relating to students' engagement in small group discussions. The results showed that student engagement in small group discussions at SMAN 1 Salimpaung can be high, with an overall mean of 2.94. Specifically, the cognitive engagement dimension showed the highest level of engagement, indicating students' active engagement in critical thinking, analyzing information, developing an understanding of the material discussed, monitoring progress and self-evaluation during small group discussions. In addition, the behavioral engagement dimension also showed significant levels of engagement, with students exhibiting behaviors that reflected active participation and interaction. Although the emotional engagement dimension showed high levels of engagement overall, there was considerable variation in students' emotions within the small group discussions